Kesantunan Berbahasa Antar Agen UKM FKIP MENGAJAR ULM - Zahiya Zahiya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Language politeness is behavior that reflects personality and culture in using good language and courtesy when interacting. This study aims to examine and describe the use of language in the communication culture between FKIP Teaching ULM SME Agents, so as to emphasize the use of language in the communication culture that prevails in society. The method used in this study is a descriptive method so that the author explains specifically what has been researched with a qualitative approach because this research is based on data in the form of words. The object of this research focuses on the speech of FM agents who speak polite language. The source of the data was obtained through voice recordings using wiretapping techniques. The results of this study show that FM agents speak politely to their speaking partners.